Broadband services to the end users - Eltaif, Tawfig; Haretha, Ahmed Ba; Mohan, Anitha; Khonji, Abdulrahman; Hamida, Belal Ahmed; Bakarman, Hesham (2013)
This article introduces a study on wavelength division multiplexed passive optical network (WDM-PON). First, we have simulated downstream transmission signals for long reach WDM system taking into account the effect of four-wave mixing (FWM), and then we have simulated downstream broadband signals. The focus in this work was set on data rate based optical transmission systems with a varying number of channels in order to investigate the potential of 0.64 Tb/s technologies for the implementation in the next generation optical transmission networks. Simulation results show that error-free operation can be achieved in long reach transmission.